Essar Steel India Limited : managing and turning around a distressed firm in insolvency - Agarwalla, Sobhesh, (SAGE Business cases., 2024)
The case has been written from the standpoint of the Alvarez and Marsal (A&M) India team that was appointed as the Chief Restructuring Agency/Officer to manage the insolvency resolution process of Essar Steel India Limited (ESIL). The committee of creditors (lenders) brought in the A&M team to manage operations while preparing the company for a competitive bidding process. As the restructuring agency/officer, A&M had to manage the day-to-day operations, engage with stakeholders across the value chain, ensure liquidity to sustain operations, run the project office to support critical projects, and manage the sale process. The case discusses the challenges faced by A&M and the series of activities undertaken by A&M to smoothen the operation of ESIL in order to maximise recovery for financial creditors. ESIL was the fourth-largest integrated steel company in India. It was admitted to the corporate insolvency resolution process (CIRP) in 2017. ESIL was one of the first 12 firms that were identified as defaulters by India’s central bank, the Reserve Bank of India (RBI). The RBI had asked the lending financial institutions (banks) to file a bankruptcy petition under the IBC, 2016. ESIL had a debt-in-default of more than INR 490 billion. In July 2017, the promoters of ESIL unsuccessfully challenged RBI’s decision to admit ESIL into insolvency proceedings. ESIL was admitted to insolvency proceedings on August 2, 2017. Although several cases discuss the decision of taking a going concern entity into the CIRP, distribution of sales proceeds among creditors, and investment strategies, this case is a comprehensive one that documents the entire gamut of activities that were undertaken in the insolvency resolution process of a large company immediately after India enacted a new law-the Insolvency and Bankruptcy Code, 2016 (IBC, 2016)-for dealing with financially distressed firms. The case covers the entire journey of A&M from the date of its appointment as restructuring of